Chemical control of Aedes aegypti: A review on effects on the environment and human health - Oliveira, Stefany Rodrigues de; Caleffe, Ronaldo Roberto Tait; Conte, Helio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2017)
Aedes mosquitoes are known to be infected by arboviruses causing disease such as dengue, zika fever, and chikunguya fever, and subsequently transmit them, to humans through the bite of infected females. Chemical control is a measure adopted as part of sustainable management and integrated vector control for public health. There are four principal classes of insecticides used for controlling mosquitoes, all being neurotoxic: organochlorides, organophosphates, carbamates, and pyrethroids. The objective of this work was to review reports on the environmental effects of the insecticides most commonly used for controlling Ae. aegypti. This bibliographic study was conducted using articles and books available in the literature with no time restriction. The databases accessed were: Google Scholar, Pubmed, SciELO, and ScienceDirect. These insecticides exhibit toxicity to the environment, and may accumulate in food and water and in the body of vertebrates. Resistance to different insecticides is a problem when the mode of control is chemical, because insects survive insecticide application and higher doses are necessary for controlling the vectors. Considering these results, the ideal method would be the newly proposed means of mosquito control using technology related to modern biotechnology.